Rational approach to the selection of conditions for diastereomeric resolution of chiral amines by diacid resolving agents - Ferreira, Frederico (Elsevier, 2006)
This paper presents an experimental and modelling approach to understanding the key conditions for diastereomeric resolutions of chiral amines by diacid resolving agents. The model is used to calculate resolution yields and enantiomeric excesses on the basis of acid–base chemical equilibria, formation of diastereomeric salts and their solubilities. Model parameters were determined experimen- tally and used to model predicted process variables, which were then compared to experimental resolution data as a function of the resolving agents/amine molar ratio. Based on this model, suggestions for the rational design of diastereomeric resolutions are made, highlighting the benefits of employing molar ratios higher than 1.5.